2016
DOI: 10.3389/fpsyg.2016.00094
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Activities and Information Learned at Home Link to the Exact Numeracy Skills in 5–6 Years-Old Children

Abstract: It is currently accepted that certain activities within the family environment contribute to develop early numerical skills before schooling. However, it is unknown whether this early experience influences both the exact and the approximate representation of numbers, and if so, which is more important for numerical tasks. In the present study the mathematical performance of 110 children (mean age 5 years 11 months) was evaluated using a battery that included tests of approximate and exact numerical abilities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Therefore, it is unlikely that the absence of the relation between the two methods is due to low validity or reliability. Additionally, the children's age in our study was comparable with previous home numeracy studies (e.g., Benavides‐Varela et al ., ; Segers et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is unlikely that the absence of the relation between the two methods is due to low validity or reliability. Additionally, the children's age in our study was comparable with previous home numeracy studies (e.g., Benavides‐Varela et al ., ; Segers et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has shown that the amount of parental math talk that children are exposed to is related to children's math abilities (Benavides‐Varela et al, ; Elliott, Braham, & Libertus, ; Gunderson & Levine, ; Levine et al, ; Ramani et al, ; Susperreguy & Davis‐Kean, ). These studies found that when parents used more math talk during everyday interactions, the children had better math skills.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-cultural work in European American, Chinese American, and Taiwan Chinese families has found a positive relation between numeracy activities and formal math skills [2022] (. A recent study found that home activities that encouraged numerical performance predicted performance on tasks measuring the Exact Number System, but not the Approximate Number System [23]. …”
Section: Introductionmentioning
confidence: 99%